Assessment of nitrates content in vegetables grown in South Kazakhstan Region (Shymkent city) - Orymbetova G.; Shambulova G.; Orymbetov E.; Kasymova M.; Kobzhasarova Z. (Техника и технология пищевых производств)
One of the most important goals in the sphere of food safety is quality assurance and production of safe food. Nowadays studies devoted to determination of nitrates content in locally produced plant products are of very high priority. Many researches on the influence of nitrates on human health prove that nitrates are one of the external threat sources. Mineral fertilizers can cause harm if improperly stored or used. The authors give comparative characteristics for nitrites content in plant products contrasting regulatory documents in European Union and Customs Union. They point out threshold limit values and their influence on human body. In some samples of cucumbers nitrates content exceeded threshold limit values. Long nitrate consumption even in small amounts is one of the important chemical risk factors for the population health as it decreases organism resistance to the influence of such external environmental factors as ecological and social ones. The research was carried out in South Kazakhstan Region. To conduct the research the authors took the samples of locally produced plant products. They determined the levels of nitrates content in the main local food products, assessed the risks of harmful impact of the controlled nitrates which come with plant products grown in South Kazakhstan Region. The results show that it is necessary to carry out constant control to ensure foodstuff safety. The authors classified food products according to their contribution to the total exposure value. Thus, the authors found out that among locally produced vegetables potato and cabbage had the highest values (61.16% and 12.1% respectively). HQmed and HQ90 values were less than 1. The authors pointed out the main ways to reduce nitrates content in plant products in the article.